2013
DOI: 10.1371/journal.pone.0069987
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical, Ultrastructural and Functional Analysis of Axonal Regeneration through Peripheral Nerve Grafts Containing Schwann Cells Expressing BDNF, CNTF or NT3

Abstract: We used morphological, immunohistochemical and functional assessments to determine the impact of genetically-modified peripheral nerve (PN) grafts on axonal regeneration after injury. Grafts were assembled from acellular nerve sheaths repopulated ex vivo with Schwann cells (SCs) modified to express brain-derived neurotrophic factor (BDNF), a secretable form of ciliary neurotrophic factor (CNTF), or neurotrophin-3 (NT3). Grafts were used to repair unilateral 1 cm defects in rat peroneal nerves and 10 weeks late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 91 publications
9
67
0
Order By: Relevance
“…However, an increasing number of studies have shown that co-delivery of multiple factors, rather than a single factor, holds greater therapeutic promise for promoting nerve regeneration because peripheral nerves contained different neuronal and glial subpopulations. 4,20,22,23 In the present study, overexpression of the c-Jun gene in SCs significantly increased the expression and secretion of multiple NFs, including GDNF, BDNF, Artn, LIF, and NGF. In addition, the c-Junmodified SCs significantly increased the average length of axons and the average area occupied by DRG axons in the coculture system, highlighting their potential to promote neuronal survival, axonal regeneration, and functional recovery in response to PNS injury.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, an increasing number of studies have shown that co-delivery of multiple factors, rather than a single factor, holds greater therapeutic promise for promoting nerve regeneration because peripheral nerves contained different neuronal and glial subpopulations. 4,20,22,23 In the present study, overexpression of the c-Jun gene in SCs significantly increased the expression and secretion of multiple NFs, including GDNF, BDNF, Artn, LIF, and NGF. In addition, the c-Junmodified SCs significantly increased the average length of axons and the average area occupied by DRG axons in the coculture system, highlighting their potential to promote neuronal survival, axonal regeneration, and functional recovery in response to PNS injury.…”
Section: Discussionsupporting
confidence: 56%
“…17,18,34 Similarly, overexpression of NGF and BDNF in SCs also has beneficial effects for peripheral nerve repair. 19,20 Artn exerts multiple effects on sensory neuron generation, survival, regeneration, and functional recovery. [38][39][40][41] LIF has also been shown to play a positive role in nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques for decellularization and recellularization have been examined for pre-clinical interventions of miscellaneous tissues, e.g., small intestine [13,14], urinary bladder [15], heart valves [16], larynx [17], dermis [18], musculofascial tissue [19] and nerves [20,21]. Concerning the female internal genital tract, small patches of myometrial tissue were recently decellularized using a modified protocol that had been optimized for decellularization of blood vessels [22].…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cells and fibroblasts were isolated from rat sciatic nerve explants using established protocols (Morrissey et al, 1991;Plant et al, 2002;Godinho et al, 2013). Briefly, 8-10-week-old rats were killed using sodium pentobarbitone (150 mg/kg intraperitoneally) and the sciatic nerves removed.…”
Section: Preparation Of Primary Schwann Cell and Fibroblast Culturesmentioning
confidence: 99%